Effects of dobutamine, dopamine, phenylephrine and noradrenaline on systemic haemodynamics and intestinal perfusion in isoflurane anaesthetised horses. (30th August 2017) - Dancker, C.; Hopster, K.; Rohn, K.; Kästner, S. B.
Summary: Background: In the horse, effects of cardiovascular‐active drugs on local perfusion of the gastrointestinal tract are poorly understood. Objectives: To determine the effect of drugs commonly used to support blood pressure, on local intestinal blood flow and tissue oxygenation under isoflurane anaesthesia. Study design: In vivo randomised crossover experiment. Methods: Ten horses were anaesthetised with isoflurane. After 90 min of equilibration three doses (μg/kg bwt/min) of dobutamine (DOB 0.5/1/3), dopamine (DA 1/2/5), noradrenaline (NA 0.1/0.2/0.5) and phenylephrine (PHE 0.5/1/3) were infused for 15 min, in a randomised order, with a 45 min washout‐period. Blood flow and tissue oxygenation (sO2 ) of jejunum, colon and stomach were measured using white light remission spectrophotometry and laser doppler flowmetry; heart rate (HR), mean arterial blood pressure (MAP), cardiac output (CO) were measured and systemic vascular resistance (SVR) calculated. Results: Compared to baseline high dose dobutamine significantly increased CO, HR, MAP (P<0.001) and blood flow to the jejunum (+47 ± 26%, P = 0.001) and colon (+29 ± 15%, P<0.001) (mean ± s.d.). Dopamine (DA5) increased CO but decreased colonic blood flow (−39 ± 21% from baseline, P<0.001), as well as SVR and MAP compared to baseline (P<0.001). Noradrenaline had no significant influence on intestinal perfusion, but increased MAP and SVR from baseline (P<0.001). Phenylephrine (PHE3) caused a significant decrease in blood flow and sO2, most profoundly at the colon compared to baseline (flow −44 ± 21%; sO2 −16 ± 3%, P<0.001), while MAP and SVR increased and CO and HR decreased (P<0.001). Main limitations: The measurement technique only allows for flow measurements in arbitrary units, which can limit comparability to other techniques. Conclusion: At the investigated doses dobutamine improved systemic and peripheral haemodynamics, while dopamine decreased MAP and peripheral perfusion. Noradrenaline increased MAP and SVR while peripheral blood flow was maintained, phenylephrine increased MAP, but reduced both local and systemic perfusion.